Energy technology and directions for the future - Fanchi, John R.; Elsevier Science Publishers (Oxford ; Boston : Elsevier Academic Press, 2004)
Energy: Technology and Directions for the Future presents the fundamentals of energy for scientists and engineers. It is a survey of energy sources that will be available for use in the 21st century energy mix. The reader will learn about the history and science of several energy sources as well as the technology and social significance of energy. Themes in the book include thermodynamics, electricity distribution, geothermal energy, fossil fuels, solar energy, nuclear energy, alternate energy (wind, water, biomass), energy and society, energy and the environment, sustainable development, the hydrogen economy, and energy forecasting. The approach is designed to present an intellectually rich and interesting text that is also practical. This is accomplished by introducing basic concepts in the context of energy technologies and, where appropriate, in historical context. Scientific concepts are used to solve concrete engineering problems. The technical level of presentation pre.
Includes bibliographical references (p. 467-481) and index.
Keywords: Power resources; Energy development; Electronic books